Prevalence of Latent Autoimmune Diabetes in Adult Based on the Presence of GAD 65 Antibodies in North-Eastern Uttar Pradesh, India - Sangma, Himalina; Singh, Anshul; Srivastava, Anubha; Misra, Vatsala (Annals of the National Academy of Medical Sciences (India), 2022)
Objective The objective of this paper was (1) to study the prevalence of latent autoimmune diabetes in adult (LADA) in the region of north-eastern Uttar Pradesh, India, based on the positivity for glutamic acid decarboxylase 65 (GAD65) antibodies and (2) to compare the glycemic profile between GAD65-positive and GAD65-negative subjects.Materials and Methods The subjects were of more than 30 years of age, with either recently diagnosed pre-diabetes/diabetes presenting with the hemoglobin A1c (HbA1c) level of ≥5.7% or already diagnosed cases of type 2 diabetes mellitus (T2DM) who had no requirement of insulin therapy for at least 6 months from the time of their diagnosis. All the patients were natives of north-eastern Uttar Pradesh. The GAD65 test was done by the enzyme-linked immunosorbent assay. Further, the glycemic status of GAD-positive and GAD-negative subjects were compared on the basis of fasting blood sugar (FBS), fasting insulin (FI), and homeostatic model assessment for insulin resistance (HOMA-IR). The “unpaired t-test” was used to compare and assess the significance of differences between the glycemic profile of GAD65-positive and GAD65-negative subjects using the GraphPad Prism Scientific Software, San Diego, CA, United States. The p-value of <0.05 was considered to be significant.Results A total of 77 patients were included in the study, with the age group ranging from 30 to 75 years (47.81 ± 12.9 years) with the male–female ratio of 1:2.6. The prevalence of LADA was found to be 51.95%. On comparing GAD65-positive and GAD65-negative groups, a higher value of HbA1c levels and FBS were found in the former, whereas FI and HOMA-IR were found to be higher in the latter. On testing for significance of difference, only FI and HbA1c values were significant (p-value <0.0001).Conclusion LADA can no longer be considered a rare type of diabetes mellitus, with the present study showing a high prevalence of LADA in this north eastern region of Uttar Pradesh. Identification of adult-onset diabetics accurately as LADA or true T2DM is very crucial for the appropriate treatment, as LADA patients require insulin inevitably and much earlier than true T2DM patients, who can be managed mostly on oral hypoglycemic agents with seldom requirement of insulin.
Keywords: type 1.5 diabetes; slowly evolving immune-mediated diabetes of adult; double diabetes; GAD65 antibody; insulin